'No more heroes': The ILC Oxford Statement on fundamental care in times of crises. (15th December 2022) - Kitson, Alison L.; Conroy, Tiffany; Jeffs, Lianne; Carr, Devin; Huisman‐Dewaal, Getty J.; Muntlin, Asa; Jangland, Eva; Grønkjær, Mette; Parr, Jenny
Abstract: Aim: To outline the International Learning Collaborative (ILC) Oxford Statement, explicating our commitment to ensuring health and care systems are equipped to meet patients' fundamental care needs during times of unprecedented crisis. Design/Method: Discussion paper. The content was developed via a co‐design process with participants during the ILC's international conference. Key Arguments: We, the ILC, outline what we do and do not want to see within our health and care systems when faced with the challenges of caring for patients during global pandemics and other crises. Specifically, we want fundamental care delivery to be seen as the minimum standard rather than the exception across our health and care systems. We want nursing leaders to call out and stand up for the importance of building fundamental care into systems, processes and funding priorities. We do not want to see the voices of nursing leaders quashed or minimized in favour of other agendas. In turn, what we want to see is greater recognition of fundamental care work and greater respect for the people who do it. We expect nurses to have a 'seat at the table' where the key health and care decisions that impact patients and staff are made. Conclusion: To achieve our goals we must (1) ensure that fundamental care is embedded in all health and care systems, at all levels; (2) build on and strengthen the leadership skills of the nursing workforce by clearly advocating for person‐centred fundamental care; (3) co‐design systems that care for and support our staff's well‐being and which foster collective resilience rather than overly rely on individual resilience; (4) improve the science and methodologies around reporting and measuring fundamental care to show the positive impact of this care delivery and (5) leverage the COVID pandemic crisis as an opportunity for transformational change in fundamental care delivery.